Effects of seed soaking with plant growth regulators combination on the aggregation ability of shallot from seeds - Pangestuti, Retno; Sulistyaningsih, Endang; Kurniasih, Budiastuti; Murti, Rudi Hari (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2023)
The true seed of shallot (TSS) is an alternative technology to boost high-quality seeds, farming cost efficiency, and shallot productivity in Indonesia. Despite the advantages of TSS, including extended shelf life and lower seed requirements, farmer and consumer acceptance remains limited due to the genetic and physiological constraints leading to single and large-sized bulbs, as an effect of low aggregation ability. This caused shallot bulbs from TSS to have a low price and were not suitable for use as seed bulbs. This research addresses challenges in shallot (Allium cepa L. Aggregatum group) production from TSS by investigating the impact of various plant growth regulators (PGRs) treatments and different soaking time on shallot growth and aggregation ability of 'Tuk Tuk' planting from TSS. The study in Yogyakarta employed a split-plot randomized block design from July to November 2018. The main plot varied the PGRs combination (9 treatment), while the subplot used the soaking time of 4 hours and 12 hours. The results indicated that a GA₃ concentration of 100 ppm, in synergy with NAA at 50 ppm for 12 hours, effectively enhanced aggregation compared to another treatment. Notably, the 'Tuk Tuk' shallot, characterized by low aggregation ability, demonstrated improved potential through seed treatment by PGRs, which could raise the number of bulbs from one to an average of two bulbs per plant. This study enhanced shallot aggregation ability, providing valuable insights for research and developing shallot production from true seeds in Indonesia.